Kematian Bukan Akhir Dari Segalanya - Agustinus Faot; Jonathan Octavianus; Juanda Juanda (Jurnal Teologi dan Pelayanan Kerusso, 2017)
Death events are often regarded as an adverse event, tiring, painful because death picks up someone you love. When humans are abandoned by loved ones, be they husbands, wives, children, lawyers, friends, friends or extended family because death is certain to be miserable in sadness, so some people consider too much death as a detrimental, tiring, tense or torturous event. It is important to understand that death does not recognize wealth, profession, position, honor. Death picks up humans at a time that can't be realized. Grieving when experiencing death is not the best solution because no one gets up again from death because of sadness. Death also comes without asking for permission from humans, because death is part of life. But it is important for humans to fully understand that behind the death which is considered as a detrimental, sad, painful thing, there is a great joy awaiting the death of a spirit. This issue will be resolved in this article.